Rectify the impact of shorter red blood cell lifespan upon HbA1c detection values in T2DM patients: modeling and internal-external verification - Zhang, Li; Gao, Ximan; Meng, Xuying; Ma, Guangyang; Li, Jing; Wang, Weilin; Chen, Sisi; Ma, Yongjian; Yu, Pei; Zhou, Saijun (Frontiers in Endocrinology, 2025)
AimsTo determine the effect of red blood cell (RBC) lifespan variability on glycosylated hemoglobin (HbA1c) measurements in type 2 diabetes mellitus (T2DM) individuals and develop a mathematical model for adjusting HbA1c values.MethodsWe tracked glucose levels in 516 T2DM patients from Chu Hsien-I Memorial Hospital, categorized into Construction (n = 416) and Internal (n = 100) cohorts. Additionally, 165 participants from Tianjin diabetic retinopathy screening cohort, serving as the Independent cohort. RBC lifespan was determined using the CO breath test, and Hemoglobin glycation variation index (HGI) was calculated from the difference between measured and estimated HbA1c (eHbA1c). Model efficacy was evaluated using AUC, accuracy, sensitivity, and specificity.ResultsAn inflection in the HGI-RBC lifespan model occurred at 66 days, with HbA1c underestimation when RBC lifespan was below 90 days, notably in the ≤ 66 days group. This underestimation increased the risk of cardiovascular and peripheral neuropathy complications. To rectify the impact of the shorter RBC lifespan in T2DM patients, the correction formula was established as HbA1c(c) = -0.05629×RBC lifespan + 1.127×HbA1c + 3.178 (R = 0.7360) in the ≤ 66 day lifespan group and HbA1c(c) = -0.004772 × RBC lifespan + 0.7569 × HbA1c + 2.394 (R = 0.7344) in the 67 to 89 day group. The corrected HbA1c models exhibited satisfactory predictive performance in all cohorts.ConclusionsAccurate adjustment for the effects of RBC lifespan on HbA1c values in T2DM patients is expected to enhance blood glucose management and the efficacious prevention and treatment of diabetes-associated complications.Clinical Trial RegistrationChu Hsien-I Memorial Hospital of Tianjin Medical University, identifier ChiCTR2100046557.